Síntese e caracterização de catalisadores a base de Au e Cu e suas aplicações na desidrogenação do 5- hidroximetilfurfural - Cabral, Natália Mariano (2021)
Dependence on oil as a source of fuel and raw material to produce chemical products opens space for the development of catalytic systems aimed at the use of biomass. In this sense, this work aims to develop a new route to produce FDCM, a monomer used in the production of PEF bioplastic, a substitute for PET. The new reaction route is the dehydrogenation of HMF in an inert atmosphere, using catalysts of Au and Cu supported on different oxides (ZrO2, SiO2 and MgO). The advantage of producing FDCM directly from HMF is the production of H2 as a co-product. There are no reports in the literature on the use of this reaction system, but the rich literature on the dehydrogenation reaction of ethanol in an inert atmosphere serves as a basis. In the ethanol reaction, the importance of having a good knowledge of the catalyst surface is known, as the electronic density of the metallic species, the chosen support, as well as the metal-support interface control the selectivity for acetaldehyde or ethyl acetate. Thus, the following catalysts were synthesized and characterized: Au/m-ZrO2, Au/SiO2, Au/Mg(OH)2, Cu/m-ZrO2, Cu/SiO2 and Cu/MgO with different metal contents. The characterizations revealed that the support used has a major influence on the structural and surface properties of metallic nanoparticles. For gold catalysts, the largest nanoparticles were obtained in materials supported on silica, while in the other two supports, the nanoparticles are smaller. Furthermore, the surface of Au/SiO2 has fewer defects than that of Au/m-ZrO2. Finally, the TPR results of the Au/Mg(OH)2 samples revealed that above 400 °C, the formation of a metallic alloy between Mg-Au may be occurring. For copper catalysts, it was observed that Cu/SiO2 and Cu/MgO have small nanoparticles well dispersed on the support, with the largest dispersion being attributed to the copper species present in the magnesium oxide, while the Cu/ m-ZrO2 materials have larger and more agglomerated metallic nanoparticles than in the other two supports. The electronic density of copper species present on the surface of these catalysts was illustrated by the FTIR-CO technique and the calculation of the Cu0/Cu+ ratio revealed the following order: Cu/MgO > Cu/m-ZrO2 > Cu/SiO2. When applied in the reaction, using the flow and batch system, the catalyst that showed the best result, for both systems, was Au/SiO2, which had the highest selectivity for FDCM. Furthermore, the Cu/m-ZrO2 catalyst was selective only for the reaction of the aldehyde group of HMF. The results obtained in this work will serve as a basis for the improvement of the proposed system, since the selectivity to FDCM was not remarkably high, in addition to the high degradability of HMF under the conditions evaluated in this work.